Effect of thermal and mechanical cycles on the hardness and roughness of artificial teeth - Tenan, Heloísa de Paula Lemos [UNESP]; Sanitá, Paula Volpato [UNESP]; Pavarina, Ana Cláudia [UNESP]; Mima, Ewerton G. [UNESP]; Jorge, Janaina Habib [UNESP] (My University, 2015)
In this study the effects of thermal and mechanical cycles on the hardness and roughness of artificial teeth were evaluated. Materials and Methods:Specimens were prepared and stored in distilled water at 37ºC for 48 hours (n=10).The hardness and roughness readings were made in the following time intervals, according to each group:G1: after specimen storage in distilled water at 37°C for 48 hours; G2: after 600.000 constant mechanical cycles; G3: after 1.200.000 constant mechanical cycles; G4: after 2.500 thermalcycling baths, alternated between hot water (55°C) and cold water (5°C) and G5: after 5.000 thermalcycling baths, alternated between hot water (55°C) and cold water (5°C). After cycling and storage procedures, the specimens of each group were submittedto surface roughness and hardness readouts. Statistical evaluation was performed by three-way analysis of variance, complemented by the Tukey multiple comparisons of means test. The level of significance adopted was 5%. There was no significant difference between G1, G4 and G5 as regards mean roughness of different brands of artificial teeth. Groups G2 and G3 showed higher mean roughness values, and generally equivalent values in all time intervals, except for Trilux (G3> G2). Significant differences in hardness values were observed in different brands of artificial teeth, and differences in values after thermal and mechanical cycling. In conclusion, our findings suggest that thermal cyclingdid not change the roughness of the artificial teeth tested, but after the mechanical cycling the roughness values increased. Thermal and mechanical cycling influenced the hardness of the artificial teeth tested.
Keywords: Artificial Teeth; Hardness; Roughness; Thermal Cycling; Mechanical Cycling